The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1007/s00066-022-01942-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of radiosensitizing agents in the therapy of glioblastoma multiforme—a comprehensive review

Abstract: Background Glioblastoma is the most common malignant brain tumor in human adults. Despite several improvements in resective as well as adjuvant therapy over the last decades, its overall prognosis remains poor. As a means of improving patient outcome, the possibility of enhancing radiation response by using radiosensitizing agents has been tested in an array of studies. Methods A comprehensive review of clinical trials involving radiation therapy in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…With repetitive administration, there is a risk of accumulation of the substance with an increased risk of developing side effects, leading to a debate in terms of biosafety [ 40 ]. Some in vitro and in vivo studies including clinical trials have investigated the efficacy of different radiosensitizing agents in the treatment of malignant gliomas: nitroimidazoles, nicotinamide and carbogen, tipifarnib, efaproxiral, tirapazamine, halogenated bromodeoxyuridine and iododeoxyuridine, poly (ADP-ribose) polymerase proteins, motexafin gadolinium, difluoromethylornithine, interferon-alpha-2a, lovastatin, and 5-ALA [ 26 ].…”
Section: Radiodynamic Therapy (Rdt)mentioning
confidence: 99%
“…With repetitive administration, there is a risk of accumulation of the substance with an increased risk of developing side effects, leading to a debate in terms of biosafety [ 40 ]. Some in vitro and in vivo studies including clinical trials have investigated the efficacy of different radiosensitizing agents in the treatment of malignant gliomas: nitroimidazoles, nicotinamide and carbogen, tipifarnib, efaproxiral, tirapazamine, halogenated bromodeoxyuridine and iododeoxyuridine, poly (ADP-ribose) polymerase proteins, motexafin gadolinium, difluoromethylornithine, interferon-alpha-2a, lovastatin, and 5-ALA [ 26 ].…”
Section: Radiodynamic Therapy (Rdt)mentioning
confidence: 99%
“…Motexafin gadolinium (MGd), a metallotexaphyrin, is a compound of gadolinium and an expanded porphyrin that can enhance the cytotoxic effects of radiation through several mechanisms relying on the additional generation of reactive oxygen species (ROS) that catalyze the oxidation of intracellular-reducing metabolites and interference with repair mechanisms of radiation-induced damage, which lead to increased cell death. Motexafin gadolinium showed great promise for multifunctional theranostic applications, especially for glioma treatment, and so far, two-phase clinical studies combined with standard radiation treatment have been established [43]. The research results indicated that, in addition to exploiting GdNPs as a positive MR imaging T 1 contrast agent, they had been identified as valued theranostic sensitizers for radiation therapy [44,45].…”
Section: Gadolinium-based Nanoparticlesmentioning
confidence: 99%
“…Motexafin gadolinium exhibited considerable potential in the realm of multifunctional theranostic applications, mainly in the treatment of gliomas. Until now two phase clinical studied have been initiated, using this compound with conventional radiation treatment . GdNPs were used as a positive MR imaging contrast T1 as well as being recognized as valuable theranostic sensitizers for radiation therapy. , Free GdNPs are not being used for clinical purposes as they are toxic; hence, they are used as an organic chelating compound.…”
Section: Nanoparticles Used For Theranostic Purposesmentioning
confidence: 99%